2018
DOI: 10.1111/apt.14597
|View full text |Cite
|
Sign up to set email alerts
|

Impact of primary antibiotic resistance on the effectiveness of sequential therapy for Helicobacter pylori infection: lessons from a 5‐year study on a large number of strains

Abstract: H. pylori-primary resistance is increasing and represents the most critical factor affecting effectiveness. Sequential therapy eradicated 83% of strains resistant to clarithromycin and metronidazole. Reliable estimates of the effectiveness of a given regimen in patients harbouring resistant strains can be obtained only by assessing a large number of strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
2
43
0
1
Order By: Relevance
“…In a recent AP&T publication from Italy, in which 1325 cultured H. pylori strains were evaluated before sequential therapy was prescribed, Gatta and colleagues report a progressive increase in in vitro resistance to one or more of clarithromycin, metronidazole and levofloxacin over the period from 2010 to 2015, continuing a trend that started in 2001 . During this time, only 39% of strains were susceptible in vitro to all 3 of these antibiotics.…”
mentioning
confidence: 99%
“…In a recent AP&T publication from Italy, in which 1325 cultured H. pylori strains were evaluated before sequential therapy was prescribed, Gatta and colleagues report a progressive increase in in vitro resistance to one or more of clarithromycin, metronidazole and levofloxacin over the period from 2010 to 2015, continuing a trend that started in 2001 . During this time, only 39% of strains were susceptible in vitro to all 3 of these antibiotics.…”
mentioning
confidence: 99%
“…The reverse hybrid therapy (PPI plus amoxicillin for 14 days, and clarithromycin plus metronidazole for the initial 7 days) has been proposed as a means of simplifying it. 19 16 A prospective cross-sectional study conducted in Spain found very impressive eradication rates of 98% for concomitant quadruple therapy compared to 94% for bismuth-based quadruple therapy.…”
Section: Quadruple Con Comitant S Equential and Hyb Rid Ther Amentioning
confidence: 99%
“…18 Regarding the sequential therapy, which was proposed as a means of overcoming antibiotic resistance, an interesting study from Italy where H pylori primary resistance to antimicrobials tested is high showed eradication rates for 10-day sequential therapy of 97% in strains susceptible to clarithromycin and metronidazole, 96% in strains resistant to metronidazole, 93% in strains resistant to clarithromycin, and surprisingly even 83% in strains resistant to both clarithromycin and metronidazole. 19…”
Section: Quadruple Con Comitant S Equential and Hyb Rid Ther Amentioning
confidence: 99%
“…A 5‐year prospective review in Italy assessed antimicrobial resistance to clarithromycin, metronidazole, and levofloxacin before giving 10‐day sequential therapy as first‐line therapy. Even in patients with dual resistance, 10‐day sequential therapy was 83.1% effective in treating the underlying H. pylori infection . A Turkish study highlighted the role for 5 + 5 clarithromycin‐based sequential therapies in areas with low clarithromycin resistance rates, which was found to be superior to 14‐day triple therapy and BQT …”
Section: Sequential and Concomitant Therapymentioning
confidence: 99%
“…Levofloxacin remains one of the most favored second‐line therapies; however, bismuth, when available, is an increasingly successful option. Sequential therapy remains in use in areas of high resistance, but may prove challenging in terms of compliance, and is no longer recommended . Three‐in‐one formulations of bismuth quadruple therapy (BQT) may improve compliance .…”
Section: Introductionmentioning
confidence: 99%